Menyibak Problematika Badan Usaha Milik Desa: Studi Etnometodologi - Waskito, Iman; Jumaidi, Lalu Takdir; Fikri, M. Ali (Sekolah Tinggi Ilmu Ekonomi AMM, 2024)
This research aims to understand the problems of managing Village BUM. This research uses an interpretive paradigm with ethnomethodology as the methodology. The data collection techniques used in this research were observation, interviews, and documentation. The informants from this research were three people, namely the Village Head, the Chair of the Village BUM, and the Village BUM Treasurer. The results of this research show that there are at least three internal problems with BUM Desa. First, the preparation of financial reports was neglected. The results of the data analysis show that this problem is due to a lack of education and training for employees in carrying out their duties and responsibilities. However, this problem is only the impact of the next two problems. Second, the mechanism for changing the chairman of BUM Desa. The change of chairman of BUMDesa, which is the appointment of the Village Head, has the potential for a conflict of political interest in retribution. This conflict is very vulnerable to ignoring the principle of professionalism in every process of appointing a new BUMDesa chairman. Third, leadership dualism. The existence of a village head, who should encourage the form of allocation of village funds and stimulants for policies that stimulate BUMDesa business, should not interfere and even be considered a shadow chairman.